Association of Abdominal Aortic Wall Thickness in the Newborn with Maternal Factors - Iwashima, Satoru; Ishikawa, Takamichi; Akira, Ohishi; Itou, Hiroaki (American Journal of Perinatology, 2012)
Purpose The goal of the present study is to carry out prospective echocardiographic measurements of intima-media thickness (IMT) in the abdominal artery of newborns.Methods Study subjects were 96 mothers and their newborns. We measured the adjusted IMT (aIMT, mm/mm) of newborn abdominal arteries by high-resolution ultrasound and evaluated the association of aIMT with various maternal and newborn factors.Results Negative correlations were observed between aIMT and gestational age (r = − 0.678, p < 0.01) and positive correlations between aIMT and placenta-to-fetus weight ratio (r = 0.418, p < 0.01). Comparing the small-for-gestational-age (SGA) versus appropriate-for-gestational-age (AGA) categories, aIMT in the SGA (n = 14) was greater than in the AGA (n = 82), with values of [0.115 (0.117) mm/mm versus 0.084 (0.074) mm/mm, p < 0.01], respectively. A multiple linear regression analysis was performed with aIMT as a dependent variable, and significant correlations were noted with gestational age (R2 = 0.524, β = − 0.515, p < 0.001 for gestational age).Conclusion On the basis of these findings, we suggest that aIMT thickness is associated with placenta-to-fetus weight ratio and gestational age, and that increased values of aIMT in SGA may indicate presence of a latent link to cardiovascular disease that might otherwise go undetected in infancy.
Keywords: cardiovascular risk; intima-media thickness; newborn; maternal factors